The Pinecone, 1971 - Valdosta State College (Valdosta State College, 1971)
I open my eyes But do not see The bats and birds and honey bees The sea and trees and sunny skys The subtle sites and super stars The earth below, behind, before The heaven above, beyond, behold The simple things around me here All so near and all so dear Escape my mind, escape my site I open my eyes and do not see....
1971 Yearbook for Valdosta State College
Keywords: Pinecone; 1971; 1970s; yearbook